Pacifism, politics, and feminism : intersections and innovations - Kling, Jennifer, 1984- (Value inquiry book series, 2019)
This anthology explores the many and varied connections between pacifism, politics, and feminism. Each topic is often thought about in academic isolation; however, when we consider how they intersect and interact, it opens up new areas for discussion and analysis.